Legal Enforcement Against Pig Farm Waste Pollution is Reviewed from Permitting Law and Islamic Law - Fahma Pantria (Universitas Muhammadiyah Surakarta, 2023)
Due to the difficulty of disposing of pig waste, the pig farming industry in Jetiswetan Pedan Village is causing environmental problems. This research aims to find out how law enforcement handles waste disposal in cases of river pollution by pig feces in Jetiswetan Village, Klaten Regency, as well as the factors that are obstacles for the Environmental Agency in dealing with river pollution by pig feces in Jetiswetan Village. In this research, the problem of law enforcement regarding the disposal of pig waste into the Jetiswetan river in Klaten Regency will be examined in accordance with licensing laws and Islamic law. This research uses qualitative legal research in the legal field. The data source is primary information collected directly from respondents or informants. The study findings show that law enforcement in Klaten Regency regarding the discharge of pig waste into the Jetiswetan river is still inadequate. The environmental agency will enforce waste disposal laws through direct observation in the field. Efforts to overcome pollution of the Jetiswetan River by pig waste have become an obstacle for environmental institutions because there are still many entrepreneurs who do not have waste disposal sites. Apart from that, there are additional obstacles, namely lack of socialization, facilities and/or facilities. This study suggests that in enforcing the law, environmental institutions must be more assertive in preventing environmental violations, and citizens and business actors in the form of pigs must better appreciate the importance of a clean and unpolluted environment.